Do grocery feedback systems enabling access to past consumption impact individual food purchase behavior? - Heli Koski; Kai Kuikkaniemi; Mika Pantzar (The Research Institute of the Finnish Economy (ETLA), 2023)
This article empirically explores whether and how providing consumers with detailed access to their past food purchase data at different levels of aggregation affects their subsequent food purchase behavior. We employ unique data covering more than 84,000 quarterly observations on Finnish consumers' purchases of various food items from August 2018 to January 2021, as well as their usage of a digital application that provides past purchase data. The data indicate that a digital feedback application that provides consumers with detailed visual and numerical information about their past food item purchases, including both monetary and health-related measures, can impact their future purchase patterns. We find apparent food item-specific and sex-, age- and household-type-specific differences in the ways that the usage of digital feedback applications affects consumers' food purchase patterns. We find that the feedback system's usage had the most noticeable and comprehensive impact on the purchase of fruit and vegetables, which was its most promoted and salient feature and provided more detailed purchase information than that for any other food category since the launch of the feedback system. Our empirical findings thus indicate that information salience does matter.
Keywords: D12; D83; D9; O33; 330; Behavioral economics; consumer choice; bounded rationality; salience; food purchases; digital feedback applications; nudging